1981
DOI: 10.1177/004051758105100707
|View full text |Cite
|
Sign up to set email alerts
|

SEM Studies of the Chars of Flame-Retardant Treated Fabrics

Abstract: Cotton fabrics treated with two different types of flame-retardant finishes were burnt, and the chars produced were examined in a scanning electron microscope (SEM). The topographical information gathered from SEM examination provides a possible explanation of the mode of action of the polymeric finish and that of the reactive finish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Scanning electron microscopy (SEM) provides a means for examination at magnifications great enough to see changes in indi-vidual fiber structures, and has been used to study chars of cotton fabrics that had been treated with various flame retardant (FR) agents [3,4,6,7]. Natural and synthetic fibers respond differently to flame retardants and to heat, and thus have different effects on the resulting char.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) provides a means for examination at magnifications great enough to see changes in indi-vidual fiber structures, and has been used to study chars of cotton fabrics that had been treated with various flame retardant (FR) agents [3,4,6,7]. Natural and synthetic fibers respond differently to flame retardants and to heat, and thus have different effects on the resulting char.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion modifies the microscopic aspect of the treated samples. Thus, the inclusion complex and FR deposition combine chemically with the fibre to modify its intrinsic burning behaviour, as described by Chauhan et al [34]. The comparative SEM images ( Figure 13) of control sample (SEM 1) and CD-grafted sample (SEM 2), FR chemical-treated sample (SEM 3) and formed cross-linked and inclusion compound sample (SEM 4) allow the visualization of modified cellulosic fabrics.…”
Section: Evolved Gas (Ppm)mentioning
confidence: 86%
“…This can be explained in terms of far distance from the market area decreasing the probability of the farmer to practice different income sources. Hassan and Nhemachena (2008) identified that proximity to the market is an important determinant of adaptation, because the market serves as a means of exchanging information with other farmers [25].…”
Section: Distance To Marketmentioning
confidence: 99%